Faktor-Faktor yang Mempengaruhi Produktivitas Tenaga Kerja Kesehatan Medis Rumah Sakit di Kota Mataram - Lido Enggar Guntara; Siti Maryam; Muhammad Irwan (IPM2KPE, 2023)
This research is entitled to determine the influence of education, incentives, motivation, training and age on the productivity of hospital medical health workers in Mataram City. The type of research used is descriptive using a purposive sampling method, namely deliberate sampling in accordance with the required sample requirements, where the population of nurses in the city of Mataram is 2115 people and the sample of respondents used is 95 respondents, which in this study used 100 respondents. . The data collection techniques used were interviews, observation, documentation, as well as using questionnaires and the data collected was then analyzed using multiple linear regression model analysis. The research results show that partially only training does not have a significant effect, while education, incentives, motivation and age have a significant effect on the productivity of medical health workers in the city of Mataram. In conclusion, the factors Education, Incentives, Motivation, Training and Age have a significant effect on the productivity of medical health workers in the city of Mataram. Keywords: Health, Medical, Labor Productivity, Hospital